Effect of Total Amount of Metformin HCl on the Characteristics of Metformin-Ca Alginate Microspheres - Dewi Melani Hariyadi; Noorma Rosita; Tiara Jeni Rosadi (Faculty of Pharmacy, Universitas Airlangga, 2019)
Introduction: Metformin hydrochloride (metformin HCl) is an antidiabetic drug that is specifically used for type 2 diabetes mellitus (DM) and belongs to the biguanide antidiabetic drugs. Objective: The aim of this research was to determine the effect of total amount of metformin HCl on the characteristics of metformin HCl-Ca alginate microspheres using aerosolization technique. Methods: The total amount of metformin were 0.5 g (F1); 1 g (F2); 1.5 g (F3) and 2 g (F4). Drug was encapsulated into alginate and was crosslinked using CaCl2. Results: The results showed that drug loadings were 5.09%; 9.61%; 13.11%; and 15.09% respectively, while the entrapment efficiencies were 48.35%; 41.99%; 38.67%; and 30.53%. The yields were 80.92%; 74.12%; 68.27%; and 59.11% respectively. Based on the statistical analysis, it was found that there were significant differences between formulas. Particles of formulas decreased as the amount of drug increased. The resulting sizes were 1.82 μm (F1); 1.96 μm (F2); 2.1 μm (F3); and  2.97 μm (F4). Conclusion: It can be concluded that amount of drug significantly affected the characteristics of metformin-alginate microspheres.